Pemanfaatan Dark Chocolate dalam Mengurangi Nyeri Dismenorhea - Ukhti Nabila; Maylina Ayu Putri Mustofa; Irza Rahmatea; Afi Ayu Nurliyanah; Septalia Isharyanti (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2023)
Adolescence was an important period towards the next phase. This period was a period of maturation of the reproductive organs characterized by primary sexual changes. Primary sexual changes in adolescents began with the arrival menstruation. The problems that could arise due to menstruation was primary dysmenorrhea. Dysmenorrhea could interfere with the activities of young women if not handled properly. Non-pharmacological therapy by consuming dark chocolate and tamarind turmeric was an alternative in the treatment of dysmenorrhea. This research was quasi-experimental study with two groups pretest posttest design with a total sample of 15 people each. Respondent were given 80 grams of 86% dark chocolate and 150 ml of tamarind turmeric and consumed on the first day of menstruation. Pain levels was measured using the NRS before and after consuming both. Data analysis used the Wilcoxon test with p-value of 0,019 and p-value of 0,034 for units, these results indicated that there was an effect of giving dark chocolate and tamarind turmeric on reducing the dysmenorrhea. The p-value for the difference in pain reduction that p-value was 0,026. This showed that dark chocolate was more effective in reducing dysmenorrhea